Analisis Peluang dan Tantangan Penggunaan Financial Technology Sebagai Upaya optimalisasi Potensi UMKM (Studi Kasus UMKM di Nusa Tenggara Barat) - Yusuf, Al Akbar (Journal of Mandalika Literature, 2023)
This research aims to analyze and interpret the challenges and opportunities faced by financial technology (fintech) in the development of Micro, Small, and Medium Enterprises (MSMEs). The study seeks to provide an overview of the research subject, which is the MSME actors. The approach used in this research is descriptive qualitative, where data analysis is based on written information and involves opinions from the informants. Based on the interviews with MSME actors, it can be concluded that they have a good understanding of fintech as a financial service that utilizes technology and is considered beneficial for the development of MSME businesses, although not all MSME owners utilize it. The research also indicates that MSMEs need to consider barriers in adopting fintech that can affect the success of its implementation. Several factors identified as causes of low fintech adoption rates in the West Nusa Tenggara region include time constraints, lack of information and skills, security concerns, legal issues, market demand, transaction volume, and skepticism towards the technology to be used. West Nusa Tenggara was chosen as the research location due to its significant potential for MSME development, with approximately 580,168 MSMEs in the region. Furthermore, there are opportunities for MSMEs to expand their businesses through fintech, with the convenience and attractiveness offered by fintech as well as opportunities to reduce fraudulent activities. MSME actors are also aware that fintech has the potential for the future of MSMEs. Therefore, support from various parties such as the Cooperative and MSME Agency and educational institutions is needed to enhance awareness and financial literacy in optimizing the utilization of fintech.